Institutional failure in Burundi: Causes of conflict and insurgency beyond ethnicity. Issue 3 (3rd July 2021) - Kasmi, Jetnor; Khan, Mohsin
ABSTRACT: Ethnic and land conflicts have recently gained significance in peace and conflict resolution. It is imperative to understand both endogenous and exogenous factors and their relations towards the institutional, democratic, and state-building process to mediate the risks of class and land conflicts. This paper attempts to identify historical relations of land and class structure by analysing Burundi land and class conflict and its significance for peace and stability. We found that the imbalance of land ownership and class structure in a society leads to armed conflicts, leading to an outbreak of other social conflicts, including violence, forced displacement, paralyzed land governance, and power relations changes. Hence, there is a dire need to foster reintegration and reconciliation through balanced multiple diplomacies in Burundi, enhancing state legitimacy towards sustainable land tenure security, improving state capacity, and ensuring justice in the reconciliation process, in association with local and regional powers.